(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Doctor-patient interaction is an indispensable process in medical institutions. Effective communication in medical consultation contributes to a great extent to the general outcome of patients’ healthcare. However, some health practitioners and patients are bereft of the proper communicative strategies in medical discourse, especially in doctor-patient encounters. This study investigated euphemism as a discursive strategy in doctor-patient conversation. Four doctor-patient conversations that have instances of euphemism were analysed in this study. The data were recorded from Alex Ekwueme Federal Teaching Hospital, Abakaliki (AE-FETHA) using a recording device with the approval of both doctors and patients. The study applied the Critical Discourse Analysis (CDA) of Fairclough (1997) and Chouliaraki and Fairclough (1999) in the analysis of the data. The approach serves as both theory and model useful for qualitative investigation that describes and interprets discourses in a social context. Findings revealed that euphemism in medical settings is not for ornament or embellishment of language but is purposely used for different strategic functions in medical discourse such as mitigating unpleasant health nomenclature, setting a social distinction in knowledge and concealing certain medical realities. The study also shows that euphemism is used to manipulate the psychological and emotional state of patients in doctor-patient communication. The study revealed that euphemisms can be lexical, phrasal or sentential. In conclusion, proper use of euphemisms in medical consultations can enhance rapport between doctors and patients, and ultimately lead to better outcomes in healthcare delivery.